Miejsce koncepcji Aleksego Wakara w teorii racjonalnego gospodarowania - Łukawer, Edward (Wydział Prawa i Administracji UAM, 1987)
The Wakar School was one of the three great scientific schools in the field of economic theory of socialism formed in Poland on the turn of the '50 and '60. The main area of its interests was the mechanism of functioning of the economy, especially the management system. The representatives of the Waker School distinguished between the spheres of plan construction and implementation; they held that only the latter sphere may be subject to decentralization. Thus they reduced the differences between centralization and decentralization only to the character of tools applied by the center; hence, they maintained that three possible types of systems could exist: directival, parametric and mixed. As to the prices, they distinguished between programming prices — applied only in the course of the construction of a plan and serving to aggregate its elements, operative prices — serving to relay the center's objectives to the enterprises, and retail prices — referring to the means of consumption. Finally, as to the types of economic balances they mentioned the direct and indirect market balances, connecting each of them not only with the character of tools appropriate for a given type, but also with the question of who was to use a particular balance. Although in principle the Wakar School no longer exists, its pupils keep researching the economy employing the methodological approach of their master. To the research problems belong: system of stimulation and feeding, the basis and character of prices, stimulating function of consumption, subjective and instrumental structures of the economy, conditions of the mechanism of its functioning, ways of implementing system changes and the relation between the functioning of the economy its development. However, unlike in the past, the above problems are no longer the subject of a collective research work.
The place of A. Wakar's conception in the theory of rational management of the economy